2015
DOI: 10.4103/1735-3327.161458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tightening torque on the marginal adaptation of cement-retained implant-supported fixed dental prostheses

Abstract: Background:The final position of the abutment changes with the amount of tightening torque. This could eventually lead to loss of passivity and marginal misfit of prostheses. The aim of this study was to evaluate the effect of three different tightening torques on the marginal adaptation of 3-unit cement-retained implant-supported fixed dental prostheses (FDPs).Materials and Methods:Two implants (Straumann) were inserted in an acrylic block so that one of the implants was placed vertically and the other at a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…[ 5 ] considered misfit values at 100 μm. The lowest values reported as clinically usual were at 70[ 33 ] and 50 μm. [ 34 ] Oyagüe et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 5 ] considered misfit values at 100 μm. The lowest values reported as clinically usual were at 70[ 33 ] and 50 μm. [ 34 ] Oyagüe et al .…”
Section: Resultsmentioning
confidence: 99%
“…However, the other articles examined in this study suggest that the magnitude of the marginal misfit is not a reliable indicator in the prognosis of the stresses generation, once the stress distribution is more related to other factors such as screw tightening. [ 29 33 36 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ghanbarzadeh et al [28] observed that, following 10, 20, and 35 Ncm binding torques, the marginal variance of the retainers of FDPs significantly increased (p < 0.05). There was no significant difference between the marginal discrepancies of these two fasteners (p > 0.05).…”
Section: Types Of Marginsmentioning
confidence: 99%